2022
DOI: 10.1371/journal.pntd.0010768
|View full text |Cite
|
Sign up to set email alerts
|

Not all mosquitoes are created equal: A synthesis of vector competence experiments reinforces virus associations of Australian mosquitoes

Abstract: The globalization of mosquito-borne arboviral diseases has placed more than half of the human population at risk. Understanding arbovirus ecology, including the role individual mosquito species play in virus transmission cycles, is critical for limiting disease. Canonical virus-vector groupings, such as Aedes- or Culex-associated flaviviruses, have historically been defined using virus detection in field-collected mosquitoes, mosquito feeding patterns, and vector competence, which quantifies the intrinsic abil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Some studies have begun to scale this gap: one study compiled a table of results from several dozen studies of Aedes aegypti and various arboviruses (see Table 6) 27 . More recently, another study compiled a dataset of 68 experimental studies that tested 111 combinations of Australian mosquitoes and arboviruses, and analyzed biological signals in the aggregated data 28 . These types of efforts are painstaking, requiring substantial manual curation of metadata, and hundreds more experiments are reported in the literature, yet remain unsynthesized due to this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have begun to scale this gap: one study compiled a table of results from several dozen studies of Aedes aegypti and various arboviruses (see Table 6) 27 . More recently, another study compiled a dataset of 68 experimental studies that tested 111 combinations of Australian mosquitoes and arboviruses, and analyzed biological signals in the aggregated data 28 . These types of efforts are painstaking, requiring substantial manual curation of metadata, and hundreds more experiments are reported in the literature, yet remain unsynthesized due to this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study highlights that a substantial breadth and depth of vector competence data are published every year in the peer-reviewed literature, but currently, the results of these experiments have no standardized home. Other recent studies highlight that synthesis of these data is possible, despite the complexity of metadata required to describe variation in experimental protocols 6 ; however, our study highlights the challenges of recovering "findable" data from the vector competence literature. Limitations we encountered included 1) Web of Science is not a comprehensive record of this research area, and older studies in particular appear to be missing; 2) keywords we used may not have captured all of the relevant studies because of variable terminology; 3) a handful of non-English-language publications-in particular, Spanish and French language publications from Latin America and Africa, respectively-were not captured by our search terms; and 4) not all studies reported reusable experimental results and metadata.…”
Section: Discussionmentioning
confidence: 90%
“…Experimental studies simplify real-world complexities of transmission and can be used to test not only the basic compatibility of a given virus and arthropod vector species but also vector competence-the relative ability of arthropod vectors to be infected by a virus and then disseminate and transmit it to a susceptible host. 2 Despite arboviruses' evolutionary tendencies toward broad host and vector range, 1,3,4 there are complex genetic underpinnings that govern vector competence, 5 which can manifest as variation in competence between closely related species of the vector 6 or even among populations of the same species. 7 Vector competence experiments are often conducted in response to the emergence of novel pathogens or the emergence of a known pathogen in a new location with previously untested vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Drivers of these shifts may include a reduction in natural breeding habitats or resources that may favor more generalist or disturbance‐tolerant species often adapted to humans and their environment (Thongsripong et al, 2013), a redistribution of host species available for blood feeding (Burkett‐Cadena et al, 2013), and processes that favor greater adaptation of pathogens to common hosts (Burkett‐Cadena et al, 2013). Community shifts matter because many mosquito‐borne pathogens may be transmitted by multiple species (Kain et al, 2022; Turell et al, 2005), and interspecific variations in vector competency within mosquito assemblages can affect pathogen circulation and transmission outcomes (McMillan et al, 2020; Roche et al, 2013). Given the involvement of multiple species in these disease systems, a continued focus on individual vector species is insufficient for understanding and predicting transmission hazard and public health risk.…”
Section: Introductionmentioning
confidence: 99%